Numerical Solution of a Two-Dimensional Problem of Determining the Propagation Velocity of Seismic Waves in Inhomogeneous Medium of Memory Type - Tomaev Marat; Totieva Zhanna (Russian Journal of Earth Sciences, 2023)
The numerical method for two-dimensional inverse dynamic seismic problem for a viscoelastic isotropic medium is presented. The system of differential equations of elasticity for isotropic medium of memory type is considered as a mathematical model. The unknown values are the displacement, the memory function of the medium (the kernel of the integral term) and the propagation velocity of elastic waves in a weakly horizontally inhomogeneous medium. Additional information for the inverse problem is the response displacement measured on the surface. The method is based on reducing the inverse problem to a system of Volterra-type integral equations and their sequential numerical implementation. The results of the study are analyzed and compared with the analytical solution. It is shown that the results are in satisfactory agreement.